2021
DOI: 10.1002/ncp.10678
|View full text |Cite
|
Sign up to set email alerts
|

Actual postoperative protein and calorie intake in patients undergoing major open abdominal cancer surgery: A prospective, observational cohort study

Abstract: Background: Adequate nutritional protein and energy intake are required for optimal postoperative recovery. There are limited studies reporting the actual postoperative protein and energy intake within the first week after major abdominal cancer surgery. The main objective of this study was to quantify the protein and energy intake after major abdominal cancer surgery. Methods:We conducted a prospective cohort study. Nutrition intake was assessed with a nutrition diary. The amount of protein and energy consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
(56 reference statements)
0
7
0
3
Order By: Relevance
“…Deficiency in traditional nutritional evaluation and supply methods were major causes for inadequate postoperative nutrition intake. It has been reported that most patients that underwent major abdominal surgery did not consume adequate protein and energy after surgery [ 28 ]. Inadequate protein and energy intake may be correlated with poor surgical outcomes such as higher complication risk and longer hospital stay [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency in traditional nutritional evaluation and supply methods were major causes for inadequate postoperative nutrition intake. It has been reported that most patients that underwent major abdominal surgery did not consume adequate protein and energy after surgery [ 28 ]. Inadequate protein and energy intake may be correlated with poor surgical outcomes such as higher complication risk and longer hospital stay [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study with 50 patients undergoing major abdominal surgery, the protein and calorie intake in the first postoperative week was recorded. In the majority of patients, the energy and protein intake was insufficient (82% and 90%, respectively), leading to more Clavien-Dindo III complications in patients who did not meet their protein targets [53]. In terms of nutritional medicine, it must be emphasized that an early oral diet is feasible but that the oral calorie requirement is not met over a longer period of time comprising the time after discharge, even after post-inpatient, and thus initiates weight loss.…”
Section: Early Oral Delivery After Esophagectomy and Gastrectomymentioning
confidence: 99%
“…Die EOF-Gruppe zeigte einen früher einsetzenden Flatus (2,9 vs. 3,1 Tage, p = 0,013), die Länge der Krankenhausverweildauer war signifikant kürzer (8,9 ± 5,7 vs. 12,6 ± 10,2 Tage, p < 0,01). Kein signifikanter Unter-schied bestand in Morbidität und Letalität, wobei die EOF-Gruppe eine signifikant niedrigere Rate abdomineller Infektionen (3,0 % vs. 7,4 %, p = 0,044) und Anastomoseninsuffizienzen hatte (1,5 % vs. 4,9 %, p = 0,048) [29]. Eine Subgruppenanalyse auf der Basis von Alter, Geschlecht, Operationsverfahren, Lymphknotendissektion und Tumorstadium ergab ebenfalls kein erhöhtes Risiko der frühzeitigen oralen Nahrungszufuhr für die Morbidität oder die Entwicklung einer Anastomoseninsuffizienz.…”
Section: Frühe Orale Ernährung Auch Nach Gastrektomie Und öSophagusresektion Möglichunclassified
“…90 %). Bei den Patienten, die das Proteinziel nicht erreichten, wurden zudem mehr Clavien-Dindo-III-Komplikationen beobachtet [29]. Aus ernährungsmedizinischer Sicht ist die orale Nahrungsaufnahme machbar.…”
Section: Frühe Orale Ernährung Auch Nach Gastrektomie Und öSophagusresektion Möglichunclassified